Development of interactive learning media based on the JIGSAW model to enhance students’ understanding of mathematical concepts - Rully Herwindo; Sri Hastuti Noer; Sugeng Sutiarso (CV. FOUNDAE, 2025)
Background: Many students experience difficulties in understanding mathematical concepts, which negatively impacts their learning outcomes. Integrating interactive learning media with the Jigsaw learning model offers a potential solution by encouraging collaborative learning and increasing student engagement through dynamic and visual content.Aims: This study aims to develop and evaluate the effectiveness of interactive learning media integrated with the Jigsaw learning model to improve students’ understanding of mathematical concepts in the classroom.Methods: The research employed a Research and Development (R and D) approach using the ADDIE model. The population consisted of 531 ninth-grade students, with a randomly selected sample of 58 students 25 in the experimental group and 33 in the control group. Data were collected through questionnaires, interviews, expert validation, and concept understanding tests, and analyzed using validation analysis, practicality analysis, normality tests, homogeneity tests, t tests, and hypothesis testing.Result: The developed media achieved a material validity score of 84% and a practicality score of 82%. Statistical analysis showed a significant difference between the control and experimental groups (p same with 0.00), indicating the media's effectiveness in improving students’ conceptual understanding.Conclusion: Integrating interactive media with the Jigsaw model enhances students’ comprehension of mathematical concepts by addressing common challenges in collaborative learning. This approach offers practical implications for improving instructional practices and supports the integration of technology in mathematics education.